2014
DOI: 10.1038/nmat4150
|View full text |Cite
|
Sign up to set email alerts
|

Giant switchable photovoltaic effect in organometal trihalide perovskite devices

Abstract: Organolead trihalide perovskite (OTP) materials are emerging as naturally abundant materials for low-cost, solution-processed and highly efficient solar cells. Here, we show that, in OTP-based photovoltaic devices with vertical and lateral cell configurations, the photocurrent direction can be switched repeatedly by applying a small electric field of <1 V μm(-1). The switchable photocurrent, generally observed in devices based on ferroelectric materials, reached 20.1 mA cm(-2) under one sun illumination in OTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

87
1,493
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,456 publications
(1,622 citation statements)
references
References 30 publications
87
1,493
12
2
Order By: Relevance
“…[32,[34][35][36] Here, the PCE obtained from the reversely scanned J-V curve is close to that extracted from the transient current measurement, which agrees well with the trapping-detrapping model. [32] Although MAPbBr 3 crystals have an ultra-low bulk trap density, [7] defects and trap states could accumulate at the crystal surface, which is also supported by the PL study ( Figure S5, Supporting Information).…”
supporting
confidence: 82%
“…[32,[34][35][36] Here, the PCE obtained from the reversely scanned J-V curve is close to that extracted from the transient current measurement, which agrees well with the trapping-detrapping model. [32] Although MAPbBr 3 crystals have an ultra-low bulk trap density, [7] defects and trap states could accumulate at the crystal surface, which is also supported by the PL study ( Figure S5, Supporting Information).…”
supporting
confidence: 82%
“…But the low electron mobility and relatively high density of electronic trap states below the conduction band (CB) of TiO 2 increase the electron recombination rates, reducing the efficiency and stability under UV illumination of the device. Further results indicated that charge accumulation induced by ion migration in the perovskite layer could be the main cause of hysteresis 105. Hence, some alternatives were developed as ETLs to obtain efficient and better stability of PVSCs, as presented in Figure 7 and Table 3 .…”
Section: Device Structurementioning
confidence: 99%
“…[173] Employing the recently invented technique of photothermal induced resonance microscopy (PTIR), Yuan et al [174] observed a MA + ion concentration contrast between before and after poling the device. This redistribution of MA + ions induced by an external electric field clearly indicated the migration of MA + ions and Azpiroz et al [167] proposed the same on the basis of computational studies.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%